2009
DOI: 10.1111/j.1440-169x.2009.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3 in the world of cell migration

Abstract: Glycogen synthase kinase 3 (GSK3) is one of the few master switch kinases that regulate many aspects of cell functions. Recent studies on cell polarization and migration have shown that GSK3 is also essential for proper regulation of these processes. GSK3 influences cell migration as one of the regulators of the spatiotemporally controlled dynamics of the actin cytoskeleton, microtubules, and cell-to-matrix adhesions. In this mini-review, the effects of GSK3 on these three aspects of cell migration will be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 74 publications
2
77
0
Order By: Relevance
“…The proinvasive phenotype of cancer cells includes an epithelial-mesenchymal transition (EMT) state (39) and distinct cellular microstructures such as lamellipodia and invadopodia (23,28,35) responsible for cell migration and invasion. In contrast with its role in cell migration (17), GSK3b was shown to inhibit EMT in normal cells by phosphorylating and stabilizing snail, a repressor of E-cadherin transcription (40). This suggests that EMT may not be involved in the mechanism by which GSK3b inhibition suppresses the migration and invasion of glioblastoma cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The proinvasive phenotype of cancer cells includes an epithelial-mesenchymal transition (EMT) state (39) and distinct cellular microstructures such as lamellipodia and invadopodia (23,28,35) responsible for cell migration and invasion. In contrast with its role in cell migration (17), GSK3b was shown to inhibit EMT in normal cells by phosphorylating and stabilizing snail, a repressor of E-cadherin transcription (40). This suggests that EMT may not be involved in the mechanism by which GSK3b inhibition suppresses the migration and invasion of glioblastoma cells.…”
Section: Discussionmentioning
confidence: 77%
“…However, a recent study indicated both pro-and anti-invasive roles for GSK3b depending on its subcellular localization in glioblastoma (16). Despite the increasing number of studies showing its participation in cell polarity and motility (17), relatively little is known about a putative role for GSK3b in the migration, invasion, and metastasis of tumor cells. Here, we demonstrate that inhibition of GSK3b attenuates the invasion of glioblastoma cells via effects on the proinvasive cellular microarchitectures and on a pivotal pathway involving focal adhesion kinase (FAK), Rac1, and c-Jun N-terminal kinase (JNK).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of GSK3 on migration of various types of cells (e.g., neoplastic and non-neoplastic) appears to be complex. Further identification of additional GSK3 targets and more detailed studies of the pathways affecting cell migration will be necessary to clarify the function of GSK3 in cell migration (Sun et al, 2009). …”
Section: Migrationmentioning
confidence: 99%
“…To date, these include MAP1b, Tau, ACF7, and CLASP2 (49,50,52,53). It has been suggested that the polarized migration of cells in general requires local GSK3␤ inhibition at the leading edge (52,54,55). Our model (Fig.…”
Section: Crmp Expression Generates Stable Interphase Microtubules-mentioning
confidence: 99%